A Rare Presentation of Thoracic Intramedullary Chordoma with Adjacent Bone Involvement: A Case Report and Review of the Literature. (9th November 2022) - Lazim, A; Akhtar, I; Rong, Y; Arriola, A; Mollaee, M
Abstract: Introduction/Objective: Chordoma originates from remnants of the embryonal notochord, and arise in bones anywhere along the spine and skull base. The most common location was thought to be the sacrum, followed by the clivus, and to a much lesser extent the rest of the spine. However, some studies have suggested an equal distribution among the skull base (32%), mobile spine (32.8%), and sacro-coccygeal bones (29.2%). Here we report a case of chordoma involving the thoracic spine. at the level of T2. Methods/Case Report: A 63-year-old male with no significant past medical history who presented with 5-6 months of intermittent, bilateral lower extremity weakness and numbness in the trunk and lower extremities. MRI of the thoracic spine demonstrated a contrast enhancing mass at T2 vertebral level with spinal cord compression and adjacent bone destruction. T1-3 laminectomy with debulking of the tumor was performed. Microscopically, the tumor cells have a lobulated architecture and are composed of epithelioid cells arranged in cords, clusters or nests, embedded in a myxoid mucinous matrix. The epithelioid cells have a variably vacuolated cytoplasm ("physaliphorous" cells). The epithelioid cells are positive for CK AE1/3, Cam5.2, EMA and Brachyury (nuclear stain), and S100 (focal). These findings support a diagnosis of chordoma. Results (if a Case Study enter NA): N/A. Conclusion: The most important and difficult differential diagnosis of chordoma is with well-differentiated chondrosarcoma. Although both chordomas and chondrosarcomas express S100, chondrosarcomas do not express cytokeratins, EMA or brachyury. Chordomas have an aggressive clinical course and poor outcome with local extension, recurrence and even metastasis. The treatment is en block surgical resection with adjuvant radiotherapy. The extent of the initial surgical resection is the most significant prognostic factor.